Prevalence, risk factors and molecular epidemiology of carbapenem-resistant Klebsiella pneumoniae in patients from Zhejiang, China, 2008–2018. Issue 1 (1st January 2020) - Hu, Yanyan; Liu, Congcong; Shen, Zhangqi; Zhou, Hongwei; Cao, Junmin; Chen, Shi; Lv, Huoyang; Zhou, Mingming; Wang, Qiang; Sun, Long; Sun, Qiaoling; Hu, Fupin; et al.
ABSTRACT: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is emerging as a worldwide public health concern; however, the long-term molecular epidemiological surveillance of clinical CRKP in China is limited. We conducted a retrospective observational study (2008–2018) to assess the prevalence, susceptibility, risk factors and molecular epidemiology of clinical CRKP isolates. We found the prevalence of CRKP increased from 2.5%, 2008 to 15.8%, 2018. CRKP were significantly more frequent among hospitalized patients from ICU, and it was significantly more likely to be isolated from the capital city (Hangzhou) and the patients aged ≥60 years. Additionally, seasons and specimen types were associated with CRKP infections . The main CRKP sequence type (ST) was ST11, and bla KPC-2 was the most prevalent gene variant. Together these data reveal an increasing incidence and resistance trends among CRKP, especially the ST11- bla KPC-2 -CRKP, in Zhejiang, during 2008–2018. Our findings are important for hospitals to limit its dissemination and optimize antibiotic administration.